CONSTRUCTION OF GROUND REACTION CURVE OF CIRCULAR TUNNEL ON VARYING ROCK MASS QUALITY USING THREEDIMENSIONAL FINITE ELEMENT METHOD - Sulthan Sammary, Farhan
Some of the most important steps of tunnel designation is to review the quality of the rock mass to be excavated and to describe the reaction that will occur if the desired excavation is carried out. The quality of the rock mass is represented by the Rock Mass Rating (RMR) classification system, while the reaction in question is quantified as rock deformation arising from the redistribution of stress field around the tunnel. The simplest method of describing the relationship between the stress state of a rock and the deformation it causes is the Ground Reaction Curve (GRC). The ground reaction curve is created through the RS3 software which implements the finite element method in the analysis process. The rock reaction curve is represented by a Longitudinal Displacement Profile to show the displacement conditions of the tunnel wall within a certain distance from the tunnel face. There are five longitudinal displacement profiles, each of which represents the value of rock quality in a certain class. From each class, the mean value is taken as a representation of that class. From this value, the rock mass parameters needed to calculate the deformation can be derived. For the value of the depth of excavation and the size of the cross section of the opening holes are assumed to be invariant on the five rock mass qualities at a certain value. The data captured and plotted into the graph is the displacement of the roof against the tunnel face distance to produce a longitudinal displacement profile. This step is repeated five times and produces five longitudinal displacement profiles each representing the corresponding rock class. Observation of the plot results obtained shows the suitability of the shape and characteristics of the longitudinal displacement profile that will be produced if the profile is made analytically